Pengaruh Pemahaman Pajak, Love Of Money Dan Moralitas Wajib Pajak Terhadap Kepatuhan Wajib Pajak: Studi Kasus Pada Mahasiswa Universitas Pamulang, Tangerang Selatan - Rawati Wawuru; Linawati (EkoPreneur, 2024)
This research aims to determine the influence of tax understanding, love of money and taxpayer morality on taxpayer compliance. Case study students at Pamulang University, South Tangerang. This type of research uses quantitative methods. The population in this study were students at Pamulang University, South Tangerang. The sampling technique uses an accidental technique, where the sample is determined based on spontaneity factors. The sample in this study was 100 respondents. The data collection method uses a survey method, namely the author distributes questionnaires directly to respondents. The questionnaire was tested for validity and reliability before collecting research data. The data analysis technique in this research uses the classic assumption test, multiple linear regression test and hypothesis testing. Based on the SPSS Version 25 test results from the tests that have been carried out, it is known that Tax Understanding, Love of Money and Taxpayer Morality simultaneously influence Taxpayer Compliance. The Tax Understanding variable partially influences Taxpayer Compliance, the Love Of Money variable influences Taxpayer Compliance and Taxpayer Morality partially influences Taxpayer Compliance. Keywords: Tax Understanding; Love of Money; Taxpayer Morality; Taxpayer Compliance